The Challenge with Clinical Radiology Electives: Student and Faculty Perspectives Identify Areas for Improvement. Issue 4 (November 2019) - Darras, Kathryn E.; Spouge, Rebecca; Kang, Heejun; Scurfield, Kathryn J.; Harper, Leonie; Yee, Adrian; Chang, Silvia D.; Forster, Bruce B.; Nicolaou, Savvas
Purpose: To determine medical students' and radiologists' attitude toward radiology electives at a distributed medical school and identify specific areas for improvement. Methods: During a single academic year, both students and faculty preceptors were surveyed anonymously following a senior radiology elective. The survey was based on an established theoretical framework for studying the educational environment which takes into account domains: (1) goal orientation, (2) organization/regulation, and (3) relationships. Mann-Whitney tests were performed to determine if there was any difference between the overall satisfaction of students and preceptors, responses from the different elective sites and students' ratings of the domains. Statistical significance was set at P < .05. Thematic analysis was performed on the narrative comments to identify specific challenges. Results: The response rate was 82.0% for students (95/116) and 19.5% (31/159) for radiologists. There was no difference in responses based on elective site. Overall, the elective was viewed positively by both groups however students rated their experience as significantly better than their preceptors ( P = .0012). Students viewed the relationships domain more positively than both the other two (goal orientation, P = .0001; organization/regulation, P = .0038). Thematic analysis identified that the student challenges were lack of autonomy, structured teaching, and preceptor continuity and the preceptor challenges were ambiguous learning objectives/expectations and insufficient resources. Conclusions: The radiology elective challenges identified in this study provide educators with specific areas to target when updating radiology electives. A better elective experience may improve students' radiology knowledge and attitude towards the specialty as well as radiologists' interest in teaching.